Pengembangan Instrumen Tes Kemampuan Pemecahan Masalah Matematika di SMP Negeri 12 Padang - Fenny Fitrianty; Alfi Yunita; Ratulani Juwita (Rumah Jurnal IAIN Bukittinggi, 2022)
This study aims to produce a valid and reliable test instrument that can measure students' problem solving abilities. The type of research used is research and development (R&D), namely the development of test instruments to measure mathematical problem solving abilities. The development model used is the Plomp model which consists of 3 phases: 1) Preliminary Research, 2) Prototyping Phase, 3) Assessment Phase. The test subjects in this study were eighth grade students of SMP Negeri 12 Padang, totaling 9 students. Based on the experiments carried out, it was found that: 1) the mathematical problem solving test instrument was said to be